Application of photo-responsive metal-organic framework in cancer therapy and bioimaging - Zhao, Yujie; Jiang, Xian; Liu, Xu; Liu, Xinyu; Liu, Zhihui; Liu, Xiaowei (Frontiers in Bioengineering and Biotechnology, 2022)
Metal-organic frameworks (MOFs) are a class of hybrid porous crystalline materials that are assembled with metal ions/clusters and organic linkers. The fungibility of organic ligands and metal centers endow MOFs that are easy to design and synthesize. Based on their unique structure, multifarious MOFs with diverse functionalities have recently been widely applied in various research areas. Particularly striking is the application of photo-responsive MOFs in biological sensing and imaging. Notably, the photoelectronic properties make photo-responsive MOFs an ideal platform for cancer phototherapy. Moreover, ultrahigh porosities and tunable pore sizes allow MOFs to load anticancer drugs, further enhancing the antitumor efficiency. In this review, the categories and developing strategies of MOFs are briefly introduced. The application fields of MOFs in bioimaging, such as up-conversion fluorescence imaging, single/two-photon fluorescence bioimaging, magnetic resonance imaging, etc., are summarized. The working mechanism of MOFs in photo-responsive, photothermal therapy (PTT), and photodynamic therapy (PDT) are expounded. Examples of using MOFs for cancer treatment, including PTT, PDT, chemotherapy, and radiotherapy, are also demonstrated. Lastly, current limitations, challenges, and future perspectives for bioimaging and cancer treatment of MOFs are discussed. We believe that the versatile MOF will bring the dawn to the next generation of cancer treatment.